Reduction of carotid perfusion promotes inflammation of vascular endothelial cells in rabbits - SHENG Yan, LI Xiu-mao, GUO Xin, XIE Qian, HUANG Ren-jie, SHENG Xin (Jichu yixue yu linchuang, 2021)
Objective To study how does reduction of blood flow perfusion regulates cytoskeleton rearrangement and its relationship with inflammation during atherosclerosis (AS). Methods The carotid artery stenosis model was established by carotid cannula in New Zealand rabbits. The normal animals were set as control group, and animals in high-fat diet were set as high-fat group. The localization and expression of vascular inflammation-related proteins MCP-1, planar cell polarity signaling pathway-related proteins DVL2 and VANGL2, and cytoskeletal proteins BBS8 and γ-tubulin were determined by immunohistochemistry staining,qPCR and Western blot. Results The cannula group and high-fat group but not control group showed intimal hyperplasia.The localizations of DVL2 and VANGL2 were found mainly at the endovascular hyperplasia in the cannula group, while the positive localizations of them were hardly found in the other two groups. Moreover, the expressions of the seproteins have been significantly up-regulated in the cannula group as compared to that in the control or high-fat group. Conclusions Reduction of blood flow perfusion is involved in the early inflammation of AS by increasing expression of MCP-1, and regulates the BBS8 and γ-tubulin during the rearrangement of microtubule cytoskeleton.